Self-Efficacy In Hypertension Patients At One Of The Public Health Centers in Garut Regency - Nugraha, Bambang Aditya; Sulastini, Sulastini; Ramdhanie, Gusgus Ghraha (Karsa Husada Health Institute Garut, 2025)
Hypertension is one of the cardiovascular diseases where there is a persistent increase insystolic and diastolic pressure. The long-term impact of hypertension is damage to variousvital organs such as the heart, brain, kidneys, etc. Therefore, hypertension patients must haveself-efficacy to prevent complications. The purpose of this study is to identify the self-efficacyprofile of patients with hypertension at one of the community health centers in Garut Regency.The research design are descriptive quantitative with sample size of 64 people throughpurposive sampling based on proportioned formula. Data collection was conducted using aquestionnaire about self-efficacy in hypertensive patients. The research results show that 35patients (55%) have low self-efficacy. Health centers are advised to develop strategies toimprove the self-efficacy of hypertensive patients to prevent complications.